1983
DOI: 10.1007/bf00397711
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine short-chain acyltransferase in pea mitochondria

Abstract: Carnitine acetyltransferase was shown to be present in pea-cotyledon mitochondria. Acetyl-carnitine may well be exported, without excessive energy loss, from mitochondrial matrix sites to extra-mitochondrial sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Overall, our observations imply that ACL is near-limiting in generating cytosolic acetyl-CoA and that other mechanisms (Wood et al, 1983;Burgess and Thomas, 1986;Masterson et al, 1990) for generating cytosolic acetyl-CoA cannot substitute for ACL-derived acetyl-CoA.…”
Section: Acl-derived Acetyl-coa Is Nonredundant In Cytosolic Acetyl-cmentioning
confidence: 65%
“…Overall, our observations imply that ACL is near-limiting in generating cytosolic acetyl-CoA and that other mechanisms (Wood et al, 1983;Burgess and Thomas, 1986;Masterson et al, 1990) for generating cytosolic acetyl-CoA cannot substitute for ACL-derived acetyl-CoA.…”
Section: Acl-derived Acetyl-coa Is Nonredundant In Cytosolic Acetyl-cmentioning
confidence: 65%
“…other acyl-CoAs across these organellar membranes (Wood et al, 1983;Burgess and Thomas, 1986;Masterson et al, 1990;Schwabedissen-Gerbling and Gerhardt, 1995;Masterson and Wood, 2000). Most of these studies were undertaken with the goal of determining whether the mitochondrial acetyl-CoA pool can be translocated to the chloroplast as acetylcarnitine, rather than to establish the export of acetylCoA from mitochondria into the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…It is suprising that Roughan et al (1993) found no CAT activity in homogenates of pea shoots and spinach and amaranthus leaves as it is fairly well established that mitochondria at least possess CAT activity Wood et al 1983;Burgess & Thomas 1986;Gerbling & Gerhardt 1988;Budde et al 1991) and this mitochondrial CAT should have been detected.…”
Section: Discussionmentioning
confidence: 99%
“…CAT has been detected in pea (Pisum sativum L.) mitochondria (Thomas & McNeil 1976;Wood et al 1983;Burgess & Thomas 1986;Gerbling & Gerhardt 1988;Budde et al 1991). Burgess & Thomas (1986) demonstrated that this CAT was located on the matrix side of the mitochondrial inner membrane, where it was able to alleviate acetyl CoA pressure and pyruvate dehydrogenase inhibition during inhibition of the Krebs cycle.…”
Section: Introductionmentioning
confidence: 99%